(untitled) (Research, Society and Development, 2023)
Diabetic foot is one of the main complications of diabetes, and occurs due to changes in musculoskeletal and sensory functions. This complication impairs the patient’s quality of life and has a high disabling power, which can lead to lower limb amputations and psychological and social harm. The prevention of these ulcerations should be the main focus of nurses, who work directly in the care of patients with DM. Therefore, the objective is to identify which interventions are carried out by nurses to prevent diabetic foot in people with diabetes mellitus. This is an integrative review carried out in the databases: SCIELO, LILACS, MEDLINE and BdENF using the descriptors “Diabetic Foot” and “Nursing care”. The search resulted in a sample of 11 articles, which showed that the nursing consultation is one of the main effective technologies for the prevention of diabetic foot, and allows the proper evaluation of the patient, mainly of the feet, as well as the realization of health education , which works effectively to involve the patient in therapy, increase self-care and consequently prevent ulcerations. It is concluded that the assessments carried out by the nurse have a positive impact on the prevention of diabetic foot and future complications, as it encourages self-care and involves the patient in their therapeutic plan.